The Cambridge grammar of classical Greek. A new reference grammar for classical Greek: Aims and principles - Van Emde Boas, E; Rijksbaron, A; Huitink, L; De Bakker, M (Cambridge University Press (CUP), 2019)
We are grateful to the editor of JCT for offering us the opportunity of outlining our views on the need for a new Greek reference grammar, to discuss our methodological principles, and to offer some thoughts on how the book may be useful as a teaching resource.